2019
DOI: 10.1186/s12885-019-6449-8
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic ablative radiotherapy and systemic treatments for extracerebral oligometastases, oligorecurrence, oligopersistence and oligoprogression from lung cancer

Abstract: BackgroundStereotactic irradiation (SBRT) is a standard of care for inoperable stage I lung cancer and brain oligometastases from lung cancer but is controversial for extracranial oligometastases. We assessed outcomes of lung cancer patients with extracranial metastases in oligometastatic, oligorecurrent, oligopersistent and oligoprogressive settings (“oligometastatic spectrum”) under strategies using SBRT +/− systemic treatments.MethodsA retrospective multicentric study of consecutive lung cancer adult patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Since lymph nodes and lung are also very frequent sites of metastatic involvement in NSCLC, it is not surprising that they showed a higher frequency of OPD in our series ( Table 2). On the other hand, liver OPD was rare in our patients (Table 2), which parallels the rarity of hepatic oligoprogression in EGFR-mutated NSCLC [4,5] and is in line with the lower immune reactivity and worse prognosis of hepatic metastases and hepatic oligoprogression in NSCLC [33][34][35].…”
Section: Discussionsupporting
confidence: 81%
“…Since lymph nodes and lung are also very frequent sites of metastatic involvement in NSCLC, it is not surprising that they showed a higher frequency of OPD in our series ( Table 2). On the other hand, liver OPD was rare in our patients (Table 2), which parallels the rarity of hepatic oligoprogression in EGFR-mutated NSCLC [4,5] and is in line with the lower immune reactivity and worse prognosis of hepatic metastases and hepatic oligoprogression in NSCLC [33][34][35].…”
Section: Discussionsupporting
confidence: 81%
“…Major exclusion criteria included other previous thoracic radiotherapy or prior TKIs therapy. Oligometastatic disease was defined as the presence of ≤5 lesions in 1 to multiple organs at the initiation of TKIs, while poly-metastatic disease was defined as > 5 metastatic lesions [18]. Oligoprogression was defined as being in a polymetastatic state with progressive lesions, while all other lesions were controlled with TKIs.…”
Section: Patientsmentioning
confidence: 99%
“…Oligoprogression was defined as being in a polymetastatic state with progressive lesions, while all other lesions were controlled with TKIs. Oligopersistence was defined as stable residual disease sites (in five or fewer sites) after systemic treatment [18,19].…”
Section: Patientsmentioning
confidence: 99%
“…Over the past 30 years oligometastatic NSCLC has been recognized as a unique clinical entity [3][4][5]11,25]. Several retrospective series and some prospective studies have demonstrated the efficacy and safety of aggressive approaches in selected patients with OMD and supported the use of metastasis-directed ablative radiotherapy alone, or in addition to a primary therapy to consolidate all sites of gross disease [26][27][28][29][30][31][32]. In addition, results from recent Phase II randomized trials have revealed a potential benefit for ablative RT in prolonging PFS [12] and OS [13,14].…”
Section: Discussionmentioning
confidence: 99%